An Unusual Presentation of Endometrial Cancer with Bilateral Adrenal Metastases at the Time of Presentation and an Updated Descriptive Literature Review - Maisie Ryan; Alexandros Laios; Darshana Pathak; Michael Weston; Richard Hutson (Case Reports in Obstetrics and Gynecology)
In endometrial cancer (EC), adrenal metastases are rare indicating advanced disease. We report an unusual presentation of EC with solitary adrenal metastases at the time of diagnosis and provide with an updated literature review. A 68-year-old woman was referred with postmenopausal bleeding of several weeks’ duration. Imaging revealed a heterogenous uterine mass and bilateral malignant adnexal masses. Hysteroscopy, endometrial biopsies, and radiological guided biopsies of the adrenal masses confirmed poorly differentiated EC. A PET-CT reported both adrenal metastases being hypermetabolic and suspicious for malignancy. The patient received six neoadjuvant chemotherapy cycles with Carboplatin and Paclitaxel. A repeated CT scan confirmed size reduction for both primary tumour and metastases. The adrenal metastases were no longer PET-avid on repeat PET-CT scan. The patient received a course of hormonal treatment and as per adrenal MDT, she underwent total laparoscopic hysterectomy and bilateral salpingo-oophorectomy followed by bilateral retroperitoneal laparoscopic adrenalectomy two months later. The patient remains asymptomatic on maintenance hydrocortisone 18 months post diagnosis. This is the first report of solitary synchronous adrenal metastases in a patient with EC. Central MDT review is key in providing individualised treatment recommendations of such rare entity.